Dynamics of the Relationship of Political Parties and Cultural Patron Clients - Anita Firdausul Husen (JURNAL PENDIDIKAN IPS, 2024)
The relationship between political parties and patron-client culture in Indonesia has quite complex dynamics. These dynamics are influenced by various factors, including social, economic, and political factors. At the social level, patron-client culture is still quite strong in Indonesian society. This is caused by factors such as poverty, economic inequality, and low levels of education. At the economic level, rapid economic development can improve people's welfare and reduce people's dependence on political parties. However, uneven economic development can increase economic inequality and worsen patron-client culture. At the political level, an undemocratic political system can make it easier for political parties to take advantage of patron-client culture to seize power. Conversely, a democratic political system can limit patron-client practices in politics. The relationship between political parties and patron-client culture has complex impacts, both positive and negative. The positive impact of this relationship is that it can increase people's political participation. The negative impact of this relationship is that it can damage the political system, because it can lead to corruption, collusion, and nepotism. To overcome the negative impacts of this relationship, efforts are needed to strengthen a democratic political system. In addition, efforts are also needed to improve people's welfare and reduce economic inequality.